Model of a QoS based on convolutions for a network based on the Internet of Bio-Nano Things - Nieto Chaupis, Huber (2017)
In this paper, the Quality of Service (QoS) for a concrete network based in the prospective idea of the Internet of Bio-Nano Things (IoBNT) is estimated. We use the well-known mathematical convolution for the segments of the network. This methodology is applied using the simple definition of efficiency per segment. The first segment assumes the communication between nanosensor and intra-body device, whereas in the second one the intra-body device is engaged to the bio-cyber interface through the THz band. Others segments belong to the macroscopic scale but working in the MHz band. When the full QoS is estimated and assuming the most optimistic scenario, our crude estimation for the concrete case applied to nanomedicine has turned out to to be of order of 85%. In the other side, the lowest values of QoS would yield numbers below 50% by which the network might be running in those scenarios where traffic in cloud might degrade the IoBNT substantially.